Tanatorio, Bonaduz. (2000)
Capilla mortuoria en el centro de la colina, cuyo acceso se sitúa entre la iglesia y el cementerio del pueblo.
Keywords: KEREZ, CHRISTIAN; SUIZA; GRAUBÜNDEN; BONADUZ; ARQUITECTURA FUNERARIA; CAPILLAS; CONSTRUCCION; MATERIALES; HORMIGON ARMADO; ILUMINACION